Concrete Durability Cementitious Materials and Reinforced Concrete Properties, Behavior and Corrosion Resistance - Rendon Diaz Miron, Luis Emilio; Koleva, Dessi A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book describes the newest developments in the creation of concrete using smart additives and supplementary cementitious materials as well as methods, technology and novel admixtures to monitor, evaluate and control steel corrosion in reinforced concrete. Industry experts and research specialists explain the structural, physical, and chemical properties of various types of concrete and its applications. They detail the characteristics preferred for manufacturing specific types of concrete. The book chapters also focus on the electrochemical state of the steel reinforcement in view of steel corrosion and corrosion control. The book encompasses main aspects as follows: Characterizes supplementary cementitious materials used for making concrete; Details the properties of concrete and the components, essential for concrete manufacturing including Portland cement, calcium sulfate, fly ash, and cupola slag; Explains the necessary treatments for the preparation of concrete during the manufacturing process. Describes the major durability-related challenge for reinforced concrete structures i.e. chloride-induced steel corrosion, in view of sensors and sensor technology for early corrosion detection. Defines stray-current induced corrosion and the consequences for both steel and concrete bulk matrix. Illustrates the potential of hybrid nano-materials to affect both steel and concrete, targeting corrosion control and superior performance of reinforced concrete structures. Targets dissemination of fundamentally substantiated mechanisms and verification of innovative applications, in view of bringing confidence for industrial utilization of novel solutions or practices in civil engineering.
The Effect of Microorganisms on Concrete Weathering -- Influence of Sulfur Ions on Concrete Resistance to Microbiologically-Induced Concrete Corrosion -- The Onset of Chloride-Induced Corrosion in Reinforced Cement-Based Materials as Verified by Embeddable Chloride Sensors -- The Influence of Stray Current Flow on the Maturity Level of Cement-Based Materials -- Electrochemical Tests in Reinforced Mortar Undergoing Stray Current-Induced Corrosion -- The Effect of Nitrogen-Doped Mesoporous Carbon Spheres (NMCSs) on the Electrochemical Behaviour of Carbon Steel in Simulated Concrete Pore Water -- Activated Hybrid Cementitious System Using Portland Cement and Fly Ash with NA2SO4 -- Optimum Green Concrete Using Different High Volume Fly Ash Activated Systems.
Keywords: Building materials; Chemistry, Technical; Structural Materials; Building Materials; Industrial Chemistry